1996
DOI: 10.1074/jbc.271.34.20223
|View full text |Cite
|
Sign up to set email alerts
|

N-Ethylmaleimide-sensitive Factor Acts at a Prefusion ATP-dependent Step in Ca2+-activated Exocytosis

Abstract: An ATP-dependent activity of NSF (N-ethylmaleimidesensitive factor) that rearranges soluble NSF attachment protein (SNAP) receptor (SNARE) protein complexes was proposed to be the driving force for membrane fusion. The Ca 2؉-activated fusion of secretory vesicles with the plasma membrane in permeable PC12 cells requires ATP; however, the ATP requirement is for a priming step that precedes the Ca 2؉ -triggered fusion reaction. While phosphoinositide phosphorylation is a key reaction required for priming, additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
129
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(140 citation statements)
references
References 26 publications
11
129
0
Order By: Relevance
“…This view agrees well with recent experiments addressing the fusion mechanism of yeast vacuole precursor vesicles (20) and of mammalian endosomes in vitro (21). A ''priming'' role for NSF would be consistent with experiments studying exocytosis in permeabilized neuroendocrine cells that show that the final steps of exocytosis are independent of ATP (22)(23)(24). The physiological role of the vesicular complex, however, remains to be established.…”
Section: Discussionsupporting
confidence: 78%
“…This view agrees well with recent experiments addressing the fusion mechanism of yeast vacuole precursor vesicles (20) and of mammalian endosomes in vitro (21). A ''priming'' role for NSF would be consistent with experiments studying exocytosis in permeabilized neuroendocrine cells that show that the final steps of exocytosis are independent of ATP (22)(23)(24). The physiological role of the vesicular complex, however, remains to be established.…”
Section: Discussionsupporting
confidence: 78%
“…SNARE and synaptotagmin are believed to be "minimal membrane fusion machinery" in Ca 2ϩ -regulated exocytosis (1)(2)(3)(4)(5). In addition, numerous proteins are assumed to participate in the process in a modulatory manner; modulation is important for homeostatic adjustment according to physiological requirements (6 -13).…”
Section: Discussionmentioning
confidence: 99%
“…Exocytosis is the final stage of the secretory pathway and involves the membrane fusion of secretory vesicles with the plasma membrane. Extensive studies on the molecular mechanism of exocytosis have revealed that the basic mechanism of membrane fusion uses the proteins termed soluble N-ethylmaleimide-sensitive factor (NSF) 3 attachment protein receptors (SNAREs) (1)(2)(3)(4)(5). The SNARE complex consists of members of the synaptobrevin (also called vesicle-associated membrane protein (VAMP)) family on the vesicular membrane (v-SNARE) and syntaxin and synaptosome-associated protein of 25 kDa (SNAP-25) families on the target plasma membrane (t-SNARE).…”
mentioning
confidence: 99%
“…1, A-C) are consistent with prior observations regarding the role of VAMP in exocytosis and now document the participation of VAMP in another exocytic process, the translocation of H ϩ -ATPase in renal epithelial cells. In neuronal cells, regulated exocytosis is thought to be mediated by the close interaction between the v-and t-SNAREs with the formation of a docking complex (20 S complex) comprised of the v-and t-SNAREs, NSF, and SNAP followed by ATP-mediated priming and Ca 2ϩ -dependent fusion (29,30). We have attempted to identify a similar 20 S-like complex in the IMCD cells.…”
Section: Snare Proteins Regulate H ϩ -Atpase Exocytosis In Imcd Cellsmentioning
confidence: 99%